Simulation Modelling as a Tool for Automotive Wiring Assembly Optimisation: Application in Real Case Studies - Adel, M.; El-Zahry, R.M.; Heshmat, M. (The South African Journal of Industrial Engineering, 2025)
Discrete-event simulation is a valuable tool for optimising production plants. The present study explores an automotive power cable wiring assembly line’s process through four real case studies, modelled using actual production data and simulated in ARENA software. Statistical analysis using PRISM identified bottlenecks, waiting times, and work-in-progress, offering key insights for improvement. The models are adaptable to other assembly lines, with potential advancements in scheduling and machine learning. By combining simulation modelling and statistical validation, the study provides practical recommendations to enhance efficiency, reduce waste, and improve performance in automotive manufacturing.